Virtual site acceptance test platform for IEC 61850 based substations with multi‐vendor bay solutions. Issue 15 (23rd August 2018) - Chen, Linwei; Charton, Thomas; Li, Haiyu; Zhang, Ray
Abstract : IEC 61850 conformance alone does not necessarily guarantee interoperability of devices from different manufacturers. Achieving full interoperability in a substation protection and control system involving different vendors will increase the confidence of power utilities to deploy digital bays or substations on site. This study presents the development of a virtual site test platform to assess the engineering process and interoperability performance for a fully digital substation with multi‐vendor bay solutions. A data monitoring tool has been developed to visualise data flows in IEC 61850 networks, which can help commissioning engineers to intuitively validate signals like they do for conventional schemes. Case studies are presented to investigate the interoperability of sampled values, generic object oriented substation events and manufacturing message specification communication services. The learning from the system integration and testing will help utilities identify potential issues in engineering phases and hence reduce the risks associated with future site tests.